O novo patrimônio católico: a projeção de uma atuação pastoral para uma cidade em mudança (1894-1953) - Nóbrega, Lucas Gomes (2020)
The present work analyzes the strategies adopted by the Catholic Church for the rearticulation of its pastoral action during the process of socio-cultural changes and urban transformations in the city of João Pessoa between the years 1894 to 1953. The historiographical debate has discussed this process, focusing on the phenomenon of romanization, which was configured as an institutional strengthening of the hierarchical structures of the Roman clergy in reaction to the thus understood secular and anticlerical threats after the end of the 19th century. Our analysis is based on the emergence of a series of institutions and buildings administered or linked to the Archdiocese of Parahyba as workers' circles, schools, hospitals, churches, charities and orphanages, which differed from the religious institutions hitherto existing from the colonial period and imperial, since it dealt with a City in a rapid process of expansion of its urban fabric and reconfiguration of ways of life. We consider these institutions and buildings, some of them centuries old, as vestiges that demonstrate the way in which the Catholic Church has historically expressed itself in relation to a society, its different ways of thinking and acting, insofar as it has institutionally reorganized itself to try, in turn., organize spaces to be occupied by different historical subjects. Given this scenario, we scan the significant scope of the relationship that was established between the State, the Church and several private agents in the development of attitudes in the universe of the city affiliated to the interest of these different instances of power and in the very process of creating what we call new heritage Catholic in the capital of Paraíba. Going through the themes of city, church and heritage, this dissertation was developed from the area of concentration in History and Historical Culture, with the line of research Teaching History and Historical Knowledge.